Comparative study on the structure characteristics, combustion reactivity, and potential environmental impacts of coal gasification fine slag with different particle size fractions. (1st March 2022) - Guo, Yang; Ma, Chaofan; Zhang, Yixin; Zhou, Lu; Guo, Zhenkun; Miao, Zekai; Zhao, Xu; Wu, Jianjun; Guo, Fanhui
Highlights: The physicochemical properties of CGFS have obvious particle size dependence. Different model-fitting methods are adopted to confirm the kinetic parameters. The disparity of combustion reactivity is clarified from carbon and pore structure. The combustion volatility of heavy metals is related to the residual fraction ratio. The potential environmental risks of some heavy metals in CGFS should be noticed. Abstract: This study aims to further reveal the properties of coal gasification fine slag (CGFS) and provide the essential basis for the efficient and environmentally friendly utilization of solid waste CGFS. In this work, the physicochemical properties, combustion reactivity, and heavy metal environmental impact of CGFS with different particle size fractions were comparatively studied. The results show that the fractions of >115 μm (SGFS-A) and 38–75 μm (SGFS-C) contain more carbon particles with a higher disorder degree due to the low degree of gasification reaction. The increase of pore roughness with the rise of particle size fractions of CGFS could be attributed to the different carbon-mineral particles occurrence patterns in four fractions. Moreover, the kinetic parameters were determined by using different model-fitting methods. The first order reaction model could best elucidate the combustion reaction mechanism of SGFS-A. Due to the transport limitation of reaction gas through the pore structure into the carbon matrix, the three-dimensional diffusion model is the most effective mechanism for the combustion process of SGFS-B (75-115 μm), SGFS-C, and SGFS-D (0-38 μm). In addition, the overall combustion reactivity of the samples follows the sequence of SGFS-A>SGFS-D>SGFS-C>SGFS-B. The sequential chemical extraction results suggest that the combustion volatility of heavy metals is negatively correlated to the residual fraction ratio of heavy metals in different particle size fractions of CGFS. The potential adverse effects of some heavy metals in CGFS on the environment should be noticed due to the high mobility.